2014
DOI: 10.1371/journal.pone.0090868
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Potentially Infectious Tuberculosis and Multidrug-Resistant Tuberculosis (MDR-TB) among Hospital Inpatients in KwaZulu Natal, South Africa Indicate Risk of Nosocomial Transmission

Abstract: BackgroundNosocomial transmission has been implicated as a key factor in the outbreak of extensively drug resistant (XDR) and multidrug-resistant (MDR-TB) tuberculosis at Church of Scotland Hospital (CoSH), in KwaZulu-Natal (KZN), South Africa. The aim of this study was to quantify the burden of potentially infectious tuberculosis and the proportion of drug resistance among hospital inpatients throughout the province of KZN.MethodsInpatients with current cough, capable of producing sputum were selected from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
1
27
0
2
Order By: Relevance
“…8,16 We did not observe large strain clusters, indicative of recent transmission and potential poor infection control practices in health-care centers, as documented in KwaZulu-Natal, South Africa. 26 Being able to compare strains from HIVinfected patients with those in the general community provided an unprecedented opportunity to map the dynamic exchange of M. tuberculosis strains between HIV-infected and uninfected individuals in the same population. The fact that strains from HIV-infected patients were interspersed with community strains indicates that most HIV-infected patients acquired M. tuberculosis infection in the general community, with limited person-to-person transmission among HIVinfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…8,16 We did not observe large strain clusters, indicative of recent transmission and potential poor infection control practices in health-care centers, as documented in KwaZulu-Natal, South Africa. 26 Being able to compare strains from HIVinfected patients with those in the general community provided an unprecedented opportunity to map the dynamic exchange of M. tuberculosis strains between HIV-infected and uninfected individuals in the same population. The fact that strains from HIV-infected patients were interspersed with community strains indicates that most HIV-infected patients acquired M. tuberculosis infection in the general community, with limited person-to-person transmission among HIVinfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent molecular strain typing and social network analyses demonstrated that 82% of patients may have acquired their infection in hospital. Studies in the surrounding community showed no increased XDR-TB prevalence [40], reinforcing the role of hospitals and clinics as important sites of potential TB transmission. The outbreak also highlighted the risk of transmission and poor outcomes seen for people living with HIV exposed to drug resistant disease.…”
Section: Enhanced Infection Control Measuresmentioning
confidence: 92%
“…These findings indicate that variables affecting the prompt treatment of TB vary according to geographical location and population, calling for studies intended to estimate and identify area and population specific factors associated with increased delay of the patients for treatment. Delayed diagnosis of pulmonary TB is also associated with drug resistance as indicated in one study conducted in South Africa [20]. Therefore, in the present study we have estimated the total delay defined as time from onset of TB symptoms, cough being the most prominent, to initiation of anti-TB treatment among smear-positive pulmonary TB patient in South Ethiopia.…”
Section: Introductionmentioning
confidence: 96%